2015
DOI: 10.1016/j.jagp.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Is Post-Traumatic Stress Disorder Associated with Premature Senescence? A Review of the Literature

Abstract: Post-Traumatic Stress Disorder (PTSD) has major public health significance. Evidence that PTSD may be associated with premature senescence (early or accelerated aging) would have major implications for quality of life and healthcare policy. We conducted a comprehensive review of published empirical studies relevant to early aging in PTSD. Our search included the PubMed, PsycINFO and PILOTS databases for empirical reports published since the year 2000 relevant to early senescence and PTSD, including: (1) biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 97 publications
10
148
0
1
Order By: Relevance
“…Overall, the present study adds to the mounting evidence from the literature that PTSD is associated with a phenotype of accelerated immune system aging (Lohr et al, 2015). The exact mechanisms underlying these associations remain unclear, but it is likely that the psychosocial stress associated with PTSD has strong influences on the neuroendocrine system, which may directly and indirectly contribute to immune aging, for example through the hypothalamic–pituitary–adrenal axis and the sympathetic–adrenal–medullary systems (Effros, 2011; Pace and Heim, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…Overall, the present study adds to the mounting evidence from the literature that PTSD is associated with a phenotype of accelerated immune system aging (Lohr et al, 2015). The exact mechanisms underlying these associations remain unclear, but it is likely that the psychosocial stress associated with PTSD has strong influences on the neuroendocrine system, which may directly and indirectly contribute to immune aging, for example through the hypothalamic–pituitary–adrenal axis and the sympathetic–adrenal–medullary systems (Effros, 2011; Pace and Heim, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…We suspect that PTSD-related MetS may reflect an underlying process wherein the stress and chronicity of PTSD symptoms contribute to accelerated cellular aging and premature disease onset (Miller et al, 2014; Lohr et al, 2015; Wolf et al, 2016). The prevalence of MetS is strongly associated with age in the US population (Ervin et al, 2009); however, we found that PTSD was associated with MetS independent of age, with a prevalence that was greater than expected by age.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigators have examined posttraumatic stress disorder in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research, in terms of methodology and findings, has been with cardiometabolic diseases. 70,71 Numerous methodologically rigorous prospective population-based observational studies have found that posttraumatic stress disorder is associated with increased risk of incident CVD [72][73][74][75][76][77][78][79][80][81][82][83][84] and T2DM. [85][86][87] However, whether and how much of the relation between childhood adversity and cardiometabolic disease may be explained by posttraumatic stress disorder is unclear, especially because these studies have included traumatic events over the life course, with a substantial proportion of studies focused on veterans and military service-related trauma, not just adversity during childhood.…”
Section: Mental Health Factorsmentioning
confidence: 99%